Numerical Simulations for Average Temperature Differential Stirling Engine - Bataineh, Khaled M. (Journal of Technology Innovations in Renewable Energy, 2013)
A second order mathematical model taken into account thermal losses for average temperature differential Stirling engine is developed. Dynamic simulation of the engine based on mathematical formulation is carried out under different operating and geometrical conditions to investigate the engine performance. The developed model is used to investigate the influence of geometrical and physical parameters on the performance of Stirling engine. Design optimization of a mean temperature differential Stirling engine is carried out. Finally optimal parameters have been determined.